Bowel obstruction in adults due to ascariasis - García, Gabriel Gutiérrez; Soto, Faustino Rubio (International Journal of Research in Medical Sciences, 2024)
In the world the most frequent and cosmopolitan parasitosis of all human helminthiasis is that caused by ascaris lumbricoides this sickness affects 1.5 billion people around the world, and approximately 60,000 people die annually as the result, about of complications, the intestinal obstruction being the most frequent complication from 38 to 87.5%, the humans become infected by ingesting the larvated eggs of the parasite. OPS report a prevalence of 46 million children between 1-year-old and 14 years old, the most importance prevalence occurs in children between 2 years old and 10 years old, decreasing significantly from the 15 years old. Mexico report through SINAVE (SEMARNAT 2020) a national incidence of 24,203 cases, the State of Sinaloa a total of 690 cases (2.8%). Lack of sanitation, drinking water and precariousness are risk factors for complications such as obstruction a complication that can progress to death.